Exploring Students’ Perception on using Live worksheet as Self-directed Learning of Listening Skills in Online Education - Yusuf, Faidah; Ali, Ameer (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
Research on the use of digital technology in promoting English Foreign Language (EFL) students’ self-directed learning of listening skills has been widely acknowledged in the literature. However, few empirical studies have been conducted on interactive worksheets as mediated instruction in the teaching of listening. This study used a qualitative method, and seventy-seven students were selected from the Education Department at State University of Makassar. This research instrument is used in interviews. Grounded in a web-based learning approach, the researchers investigated the students’ perceived experiences in conducting the “liveworksheet” website and its potential to promote their self-learning, activeness, and autonomy in listening practices. As a result, the study highlights several significant findings: students’ self-directed learning, automatic scoring, accessing the website, students’ vocabulary mastery, students’ learning autonomy, and students’ technology skills. Moreover, this study suggests employing web-based “liveworksheet” activities in a technology-mediated EFL learning environment, thus increasing their self-directed learning and ease to make distance learning happen through the website. Therefore, this study highlighted the advantages of in-making live worksheets for teachers and students in answering live worksheets which are very important to support, provide interesting learning, and get their learning outcomes